Robots with tears can convey enhanced sadness and elicit support intentions - Yasuhara, Akiko; Takehara, Takuma (Frontiers in Robotics and AI, 2023)
The behaviour of shedding tears is a unique human expression of emotion. Human tears have an emotional signalling function that conveys sadness and a social signalling function that elicits support intention from others. The present study aimed to clarify whether the tears of robots have the same emotional and social signalling functions as human tears, using methods employed in previous studies conducted on human tears. Tear processing was applied to robot pictures to create pictures with and without tears, which were used as visual stimuli. In Study 1, the participants viewed pictures of robots with and without tears and rated the intensity of the emotion experienced by the robot in the picture. The results showed that adding tears to a robot’s picture significantly increased the rated intensity of sadness. Study 2 measured support intentions towards a robot by presenting a robot’s picture with a scenario. The results showed that adding tears to the robot’s picture also increased the support intentions indicating that robot tears have emotional and social signalling functions similar to those of human tears.